Numerical simulation of surface roughness effects on the vortex-induced vibration of a circular cylinder at a subcritical Reynolds number - Wei Chen; Siying Wang; Xiaotao Shi; Chang-Kyu Rheem; Yongshui Lin; Erpeng Liu (International Journal of Naval Architecture and Ocean Engineering, 2022)
The Vortex-Induced Vibration (VIV) of a circular cylinder with different surface roughness is numerically simulated at a subcritical Reynolds number of 3900. The effects of surface roughness on the vibration response amplitude, hydrodynamic coefficients and wake vortex are analyzed. The results show that as surface roughness increases, four branches (initial, upper, super-upper and lower branches) appear in the VIV response for a smooth cylinder, and for a cylinder with a small surface roughness of KS/D=2.5×10−3 , this response changes to three branches (initial, upper and lower branches). The vortex shedding for the initial and lower branches is 2S mode, and that for the upper and super-upper branches (lock-in range) is P + S−, P+S+ and 2P modes. With increasing surface roughness, the maximum amplitude has little difference, and the width of the lock-in range increases. A large jump in the vortex phase at the transition of the initial and upper branches and a large jump in the total lift phase at the transition of the upper and lower branches are found, and these jumps are associated with a switch in the timing of vortex shedding (jump of the vortex phase: 2S mode to P + S− mode; jump of the lift phase: other modes to 2S mode). The results are significant for the development of flow and vibration control technology.